2000
DOI: 10.1076/1388-0209(200009)3841-aft298
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral, Cyototoxic And Antimicrobial Activities Of Anthraquinones Isolated From The Roots Of Morinda Elliptica

Abstract: 2-Formyl-1-hydroxyanthraquinone, along with ten other known anthraquinones (1-hydroxy-2-methylanthraquinone, nordamnacanthal, damnacanthal, lucidin-?-methyl ether, rubiadin, rubiadin-1-methyl ether, soranjidiol, morindone, morindone-5-methyl ether and alizarin-1-methyl ether), isolated from the roots of Morinda elliptica , were assayed for anti-HIV, cytotoxic and antimicrobial activites. Only damnacanthal showed moderate activity against HIV. It was cytotoxic towards the MCF-7 (breast carcinoma) and CEM-SS (T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 3 publications
2
45
0
Order By: Relevance
“…In the present result from the action of these terpenes. The only extract active against both strains (GM-MIC of 250 µg/mL) was that of M. royoc L. Extracts from other species such as M. elliptica and M. angustifolia displayed different biological activities, including antifungal (Xiang et al, 2008;Ali et al, 2000). Nevertheless, to our knowledge, the antifungal activity of M. royoc L has not been reported.…”
Section: Resultsmentioning
confidence: 71%
“…In the present result from the action of these terpenes. The only extract active against both strains (GM-MIC of 250 µg/mL) was that of M. royoc L. Extracts from other species such as M. elliptica and M. angustifolia displayed different biological activities, including antifungal (Xiang et al, 2008;Ali et al, 2000). Nevertheless, to our knowledge, the antifungal activity of M. royoc L has not been reported.…”
Section: Resultsmentioning
confidence: 71%
“…Purified compounds with \10 lg/mL of cytotoxicity concentration are considered as promising cancer chemotherapy agents (Shier 1991). This cytotoxicity is attributed to the chemical structure of DAM and NDAM, as shown by Ali et al (2000) where the chemical structure between these compounds is tightly associated and the presence of the hydroxyl group at C-1 and C-3 and/or a formyl group at C-2 in the anthraquinones structure might be responsible for their cytotoxicity effects against several cancer cell lines. The selective cytotoxic effect of DAM and NDAM was supported by several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The increased number of G 1 population is not a consequence of perturbation on G 2 arrest because the total cell number decreased and more fragmented DNAs increased over time (data not shown). Interestingly, a previous screen by Ali et al identified Dam as an agent that protects against cytotoxicity caused by HIV [30]. Their screen was performed on CEM-SS cell infected with HIV and the mechanism of inhibition has remained unknown.…”
Section: Damnacanthal Inhibits Cell Death Without Affecting Vpr's G 2mentioning
confidence: 99%